Soil Organic Matter as Catalyst of Crop Resource Capture - King, Alison E.; Ali, Genevieve A.; Gillespie, Adam W.; Wagner-Riddle, Claudia (Frontiers in Environmental Science, 2020)
The positive effect of soil organic matter (SOM) on crop yield has historically been attributed to the ability of SOM to supply crops with nitrogen and water. Whether management-induced increases in SOM meaningfully supplement water supply has received recent scrutiny, introducing uncertainty to the mechanisms by which SOM benefits crops. Here, we posit that SOM does not need to increase the supply of a growth-limiting resource to benefit crops; it only needs to facilitate root access to extant resource stocks. We highlight evidence for the ability of SOM to alleviate negative impacts of waterlogging and compaction on root development. Waterlogging restricts root aeration and, even if transient, can cause permanent downregulation of root biosynthesis. Management practices that promote SOM reduce the risk or duration of waterlogging by accelerating water infiltration, forestalling ponding, and promoting drainage. Compaction as a restriction to root development manifests in drying soils, where mechanical impedance inflates the photosynthate required to extend root tip into soil, leading to short, thick, and shallow roots. Soil organic matter reduces mechanical impedance in dry soils and is associated with root channels to the subsoil, granting crop access to deep soil water. In this framework, crop response to SOM depends on the interaction of a) crop susceptibility to waterlogging or compaction, b) soil moisture during crop maturation, and c) ‘baseline’ drainage and compaction status of soil. By exploring proposed mechanisms, future research may better constrain the context and magnitude of crop yield improvements to be expected from SOM management.